Exploring the new dimensions of selenium research to understand the underlying mechanism of its uptake, translocation, and accumulation. Issue 4 (25th November 2020) - Raina, Meenakshi; Sharma, Akanksha; Nazir, Muslima; Kumari, Punam; Rustagi, Anjana; Hami, Ammarah; Bhau, Brijmohan Singh; Zargar, Sajad Majeed; Kumar, Deepak
Abstract: Selenium (Se) is a vital mineral for both plants and animals. It is widely distributed on the earth's crust and is taken up by the plants as selenite or selenate. Plants substantially vary in their physiological response to Se. The amount of Se in edible plants is genetically controlled. Its availability can be determined by measuring its phytoavailability in soil. The low concentration of Se in plants can help them in combating stress, whereas higher concentrations can be detrimental to plant health and in most cases it is toxic. Thus, solving the double‐edged sword problem of nutritional Se deficiency and its elevated concentrations in environment requires a better understanding of Se uptake and metabolism in plants. The studies on Se uptake and metabolism can help in genetic biofortification of Se in plants and also assist in phytoremediation. Moreover, Se uptake and transport, especially biochemical pathways of assimilation and incorporation into proteins, offers striking mechanisms of toxicity and tolerance. These developments have led to a revival of Se research in higher plants with significant break throughs being made in the previous years. This review explores the new dimensions of Se research with major emphasis on key research events related to Se undertaken in last few years. Further, we also discussed future possibilities in Se research for crop improvement.